2017
DOI: 10.1002/jbm.a.36062
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional carbon nanotube scaffolds for long‐term maintenance and expansion of human mesenchymal stem cells

Abstract: Expansion of mesenchymal stem cells (MSCs) and maintenance of their self-renewal capacity in vitro requires specialized robust cell culture systems. Conventional approaches using animal-derived or artificial matrices and a cocktail of growth factors have limitations such as consistency, scalability, pathogenicity, and loss of MSC phenotype. Herein, we report the use of all-carbon 3-D single- and multiwalled carbon nanotube scaffolds (SWCNTs and MWCNTs) as artificial matrices for long-term maintenance and expan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 72 publications
(182 reference statements)
0
8
0
Order By: Relevance
“…Our previous study demonstrated for the first time that AS-MSCs outperform HD-MSCs in osteogenic differentiation when cultured in a 2D system in vitro 12 . However, some studies reported that the function of cells in 2D culture cannot completely reflect their real capacity in vivo 24 . Recently, 3D biomimetic microenvironments with different types of materials have been widely used in cellular function studies 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study demonstrated for the first time that AS-MSCs outperform HD-MSCs in osteogenic differentiation when cultured in a 2D system in vitro 12 . However, some studies reported that the function of cells in 2D culture cannot completely reflect their real capacity in vivo 24 . Recently, 3D biomimetic microenvironments with different types of materials have been widely used in cellular function studies 25 .…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, researchers have been working on the fabrication and optimization of CNT-based nano-constructs to serve as a scaffold for mesenchymal stem cells. For example, Lalwani et al fabricated all-carbon 3-D singleand multiwalled CNT scaffolds as artificial matrices for long-term maintenance and expansion of human adipose-derived human mesenchymal stem cells [154]. The fabricated scaffolds demonstrated a good level of cell viability, attachment, proliferation, and infiltration in CNT scaffolds comparable to poly(lactic-co-glycolic) acid (PLGA) scaffolds.…”
Section: Carbon Nanotubes and Stem Cellsmentioning
confidence: 99%
“…Furthermore, cells were metabolically active and the formation of filopodia and cellular extensions (Figure d, white arrows) extending outward from the cell body (black circles) was observed. It is critical for cells to attach and infiltrate the porous scaffolds and initiate the deposition of ECM proteins for effective new tissue regeneration . Collagen‐I protein acts as a binder to facilitate the attachment of cells with scaffolds and other ECM components thereby playing an essential role in cellular signaling, differentiation and tissue maturation .…”
Section: Discussionmentioning
confidence: 99%
“…It is critical for cells to attach and infiltrate the porous scaffolds and initiate the deposition of ECM proteins for effective new tissue regeneration. [43][44][45]53 Collagen-I protein acts as a binder to facilitate the attachment of cells with scaffolds and other ECM components thereby playing an essential role in cellular signaling, differentiation and tissue maturation. 54 Immunofluorescence imaging confirms that cells are able to express and secrete collagen-I protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation